Phenotyping for Genetic Improvement of Feed Efficiency in Fish: Lessons From Pig Breeding - Knap, Pieter W.; Kause, Antti (Frontiers in Genetics, 2018)
Feed incurs most of the cost of aquaculture production, so feed efficiency improvement is of great importance. Our aim is to use work done in pigs to formulate a logical framework for assessing the most useful component traits influencing feed intake and efficiency in farmed fish – either to identify traits that can together be used for genetic improvement of feed efficiency, or as substitute traits for feed intake recording. Improvement of gross feed efficiency in growing fish can be accomplished by selection for increased growth rate. However, the correlation of growth with feed efficiency is typically only modest, and hence there is room for further improvement of feed efficiency through methods other than growth selection. Based on a literature review we propose that the most effective additional methods are selection for reduced body lipid content and for reduced residual feed intake (RFI). Both methods require more or less sophisticated recording equipment; in particular, the estimation of RFI requires recording of feed intake (DFI) which is a challenge. In mammals and birds, both these approaches have been effective, and despite the high costs of daily feed intake recording, the RFI approach can be cost-efficient because maintenance requirements are high and therefore RFI variation covers a large part of DFI variance. Maintenance requirements of fish are lower and therefore RFI variation covers a smaller part of DFI variance. Moreover, accurate high-volume routine individual DFI recording is much more challenging in fish than in mammals or birds. Hence selection for reduced body fat content is likely a more effective (and certainly more cost-efficient) way to improve FCR in fish than selection for reduced RFI. As long as body fat content is dealt with as an explicit selection criterion, the only valid reason for DFI recording would be the requirement of RFI reduction. So, if RFI reduction is not required, there would be no need for the expense and effort of individual DFI recording – and in fish breeding that would be a very desirable situation. Solid evidence for these propositions is still scarce, and their generality still needs to be confirmed.